An All Solid‐State Zinc−Air Battery with a Corrosion‐Resistant Air Electrode. Issue 14 (25th April 2018) - Devendrachari, Mruthyunjayachari Chattanahalli; Basappa, Chidananda; Thimmappa, Ravikumar; Bhat, Zahid Manzoor; Kotresh, Harish Makri Nimbegondi; Kottaichamy, Alagar Raja; Varhade, Swapnil; Khaire, Siddhi; Reddy, Kallam Ramareddy Venugopala; Thotiyl, Musthafa Ottakam
Abstract: We illustrate an all solid‐state Zn−air battery by utilizing the ability of a titanium‐nitride‐functionalized molecular catalyst to mediate the oxygen reduction reaction by avoiding the parasitic corrosion chemistry and the hydroxide‐holding capacity of the Zirfon membrane. The efficient ionic communication between the half‐cell electrodes provided by the Zirfon membrane in combination with the chemical/electrochemical stability of the TiN‐based air electrode ultimately led to an all solid‐state and air‐breathing battery possessing high durability and stability. Abstract : How to avoid corrosion : A corrosion‐resistant air electrode for all solid‐state Zn−air batteries is developed using a titanium‐nitride‐functionalized molecular catalyst to mediate the oxygen reduction reaction.